Sucessão estratigráfica e tratos de sistemas do Membro Romualdo, porção leste da Bacia do Araripe, nordeste do Brasil - Custódio, Michele Andriolli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Located in northeastern Brazil, the evolution of Araripe Basin has been associated with the fragmentation of Gondwana and opening of the South Atlantic. The Santana Formation belongs to the post-rift sequence of the basin and is characterized by the presence of laminated limestones in the lower portion (Mb. Crato), evaporite (Ipubi) and siliciclastics (Mb. Romualdo). For better understanding of the Romualdo's stratigraphy, depositional environments and tract of systems, a stratigraphic analysis was made with representative columnar sections of the unit. Sedimentary facies have been described in detail, as well as paleocurrents measured at different stratigraphic levels. It was found that the contact of Mb. Romualdo with the carbonate-evaporite section (Mbs. Crato and Ipubi) is a unconformity, evidenced by residual lags and thin layers of conglomerates above the contact. Above the conglomeratic levels predominate fine sandstones / medium interlayered with calciferous green shales. The percentage of shales increases towards the top, featuring retrogradational stacking culminating in layers of coquinas, excellent stratigraphic mark in the basin. Thin layers of coquins of gastropods comprising equinoids, located on the shale section, present in three sections marine deposits are associated with surfaces ravine. The upper section is characterized by recurrent facies of green shales, sandstones intercalated with sandstones progressively become more frequent towards the top of the unit, featuring the regressive part of the cycle. The sandstones present cross-stratification, often with mud clasts and clay layers in the foresets, and beddings of flaser type and wavy in heterolitic facies, suggesting the action of tidal currents. Paleocurrents measured in the sandstones show gaps with opposite flow directions outlining bipolar standards, which reinforce the interpretation of shallow marine environment influenced by tides during the sedimentation...

Situada na Região Nordeste do Brasil, a Bacia do Araripe teve evolução associada à fragmentação do Gondwana e abertura do Atlântico Sul. A Formação Santana pertence à sequência pós-rifte desta bacia e é caracterizada pela presença de calcários laminados na sua porção inferior (Mb. Crato), evaporito (Camadas Ipubi) e siliciclásticos (Mb. Romualdo). Para melhor entendimento da sucessão estratigráfica, ambientes deposicionais e dos tratos de sistemas do Membro Romualdo, foi realizada uma análise estratigráfica, tendo sido levantadas seções-colunares verticais representativas da unidade. Fácies sedimentares foram descritas em detalhe, bem como medidas de paleocorrentes em diferentes níveis estratigráficos. Verificou-se que o contato do Mb. Romualdo com a seção carbonático-evaporítica (Mbs. Crato e Ipubi) é uma desconformidade, evidenciada por lags residuais e camadas delgadas de conglomerados acima do contato. Sobre os níveis conglomeráticos predominam arenitos finos/médios com intercalações de folhelhos verdes calcíferos. A porcentagem de folhelhos aumenta em direção ao topo, caracterizando empilhamento retrogradante que culmina nas camadas de coquinas, excelente marco estratigráfico na bacia. Camadas delgadas de coquinas de gastrópodes portadoras de equinoides, situadas sobre a seção de folhelhos, presentes nas três seções levantadas, constituem depósitos marinhos associados a superfícies de ravinamento. A parte superior da seção é caracterizada pela recorrência de fácies de folhelhos verdes, intercalados com arenitos que progressivamente se tornam mais frequentes em direção ao topo da unidade, caracterizando a parte regressiva do ciclo. Os arenitos apresentam estratificações cruzadas, muitas vezes com clastos de lama e lâminas de argila nos foresets, e acamamentos do tipo flaser e wavy em fácies heterolíticas, sugestivas da atuação de correntes de maré. Paleocorrentes medidas nos...
Keywords: Geologia estratigráfica; Facies (Geologia); Paleocorrentes; Ceara